Utilization of the Tiktok Application as a Media for Learning the History of Islamic Culture - Shanshan Xu; Xie Guilin; Deng Jiao; Zuliana Zuliana (International Journal of Educational Narratives, 2024)
Background. Teachers tend to carry out teaching and learning activities using only one learning tactic, namely lecture tactics. Even though there are many learning tactics, one of them is TikTok media Purpose. This research aims to utilize TikTok software as a student motivation tool and improve a more interesting learning style in learning the history of Islamic culture. Method. The research method that the researcher used was a quantitative method with a survey model, a survey tool using Google from and in-depth interviews. The survey used in this research was WhatsApp.    Results. This research produces a TikTok media that is applied by teachers in the teaching and learning process as a motivational tool and improves student learning achievement. Conclusion. The conclusion of this research explains that the role of TikTok really helps teachers in the teaching and learning process in Islamic cultural history subjects so that student achievement increases. The limitation of this research is that researchers can only develop the TikTok platform as a medium for learning the history of Islamic culture in one lesson and only as a motivation tool and improve student learning achievement so that it is not boring.